Personal Satellite Services 4th International ICST Conference, PSATS 2012, Bradford, UK, March 22-23, 2012. Revised Selected Papers - Pillai, Prashant; Shorey, Rajeev; Ferro, Erina (Lecture Notes of the Institute for Computer Sciences, Social Informatics and Telecommunications Engineering, 2013)
This book constitutes the thoroughly refereed post-conference proceedings of the 4th International ICST Conference on Personal Satellite Services, PSATS 2012, held in Bradford, UK, in March 2012. The 22 revised full papers presented together with 4 poster sessions were carefully reviewed and selected from various submissions. The papers cover topics such as radio resource management; spectrum/interference management and antenna design; mobility and security; and protocol performance in satellite networks.